(untitled) (Altre Modernità, 2022)
In this paper I want to investigate the textual palimpsest of Nona Fernández’s novel, La dimensión desconocida with the following aims: 1) analyze the voice and role of the ’witness’ in the construction of the text, with emphasis on the dialectical dialogue between the authorial presence and the figuration of the torturer and the importance of imagination in testimonial practice; 2 ) Trough the identification of spatial dimension as the fundamental core of the novel, explore the links between the different narrative ’scenes’ and the Museum of Memory, the metaphorical space that governs the novel’s architecture; 3) exploring the links between the different narrative ’scenes’ and the Museum of Memory, the metaphorical space that governs the textual framework. Based on these speculations, The Unknown Dimension can be thought of as a "place of memory," an alternative archive that, through imagination, recomposes the remains and approaches its vision.